ANALISIS PENGGUNAAN APLIKASI PEGADAIAN SYARIAH DIGITAL DALAM MENINGKATKAN PELAYANAN NASABAH DI PT PEGADAIAN UPS SIBUHUAN - Akhir Saleh Pulungan; Aisah Dani Pulungan; Junda Harahap; Nur Jannah Nasution (JSE: Jurnal Sharia Economica, 2026)
The purpose of this research is to examine how PT Pegadaian UPS Sibuhuan uses the Pegadaian Syariah Digital application (PSD) to enhance customer service quality. The research's backdrop is the evolution of digital technology, which forces financial institutions to change in order to offer quick, effective, and sharia-compliant services. Employees and clients of PT Pegadaian UPS Sibuhuan who have utilized the PSD application are the subjects of this descriptive qualitative study, which employs observation, interviewing, and documenting techniques. The study's findings indicate that using the PSD application can facilitate transactions, boost productivity, and provide clients more access to services. Nevertheless, there are still issues with its execution, such users' ignorance of technology and network restrictions in some places. In summary, PSD apps contribute to better customer service. Nonetheless, both new and current users must be made more aware of the usage of PSD applications, especially through ongoing infrastructural and literacy improvements.